USING THE EXPERIENCE OF KOREAN HIGHER EDUCATION INSTITUTIONS IN UZBEKISTAN - Bekimbetova Ainagul Amangeldievna; Zhaksilikova Mavlyuda Bakhramovna (Scholar Express Journal, 2022)
This article is considering questions National Higher Education Reforms of Uzbekistan and the use of the Republic of Korea for this experience in the development of higher education. Lights key changes in the education system of Uzbekistan.
Keywords: International Experience; Reform; Higher Education; Education